Real rights - Wellman, Carl (Oxford University Press, 1995)
Real Rights provides a new theory of the grounds of legal and moral rights. Wellman argues that only agents can be right-holders, that children and the mentally limited can have only limited rights, and that foetuses, the dead, and groups can have none. Real Rights also describes how rights imply duties, and how rights conflicts can be resolved and what considerations override rights